Comparison of Necroptosis With Apoptosis for OVX-Induced Osteoporosis - Bin He; Bin He; Yongjun Zhu; Hongwang Cui; Bo Sun; Tian Su; Peng Wen (Frontiers in Molecular Biosciences, 2021)
As one common kind of osteoporosis, postmenopausal osteoporosis (PMOP) is associated with the death and excessive loss of osteocytes. Estrogen deficiency of PMOP can cause osteocyte death by regulating necroptosis and apoptosis, but their roles in POMP have not been compared. In the present study, ovariectomy (OVX)-induced rat and murine long bone osteocyte Y4 (MLO-Y4) cells were used to compare the influence of necroptosis and apoptosis on osteocyte death and bone loss. Benzyloxycarbonyl-Val-Ala-Asp (zVAD) and necrostatin-1 (Nec-1) were used to specifically block cell apoptosis and necroptosis, respectively. OVX rats and MLO-Y4 cells were divided into zVAD group, Nec-1 group, zVAD + Nec-1 group, vehicle, and control group. The tibial plateaus of the rat model were harvested at 8 weeks after OVX and were analyzed by micro–computed tomography, transmission electron microscopy (TEM), the transferase dUTP nick end labeling assay, and western blot. The death of MLO-Y4 was stimulated by TNF-α and was measured by flow cytometry and TEM. The results found that necroptosis and apoptosis were both responsible for the death and excessive loss of osteocytes, as well as bone loss in OVX-induced osteoporosis, and furthermore necroptosis may generate greater impact on the death of osteocytes than apoptosis. Necroptotic death of osteocytes was mainly regulated by the receptor-interacting protein kinase 3 signaling pathway. Collectively, inhibition of necroptosis may produce better efficacy in reducing osteocyte loss than that of apoptosis, and combined blockade of necroptosis and apoptosis provide new insights into preventing and treating PMOP.